Diagnostic value of lung ultrasonographic parameters in predicting outcomes of coronavirus disease 2019 (COVID-19) in oxygen-dependent patients requiring intensive care unit treatment - K. V. Kalashnyk; M. Yu. Kolesnyk; O. V. Riabokon; V. V. Cherkaskiy (Zaporožskij Medicinskij Žurnal)
The aim – to determine the diagnostic value of lung ultrasound parameters in predicting outcomes of coronavirus disease 2019 (COVID-19) in oxygen-dependent patients requiring intensive care unit treatment.